Pediatric Orthopaedic Venous Thromboembolism - Neha Mulpuri, MD; Ryan M. Sanborn, BA; Pratik Pradhan, BS; Patricia E. Miller, MS; Maria F. Canizares, MD, MPH; Benjamin J. Shore, MD, MPH, FRCSC (JBJS Open Access, 2024)
Background:. There is growing evidence of increased venous thromboembolism (VTE) incidence in children with trauma or infection. The purpose of this study was to conduct a systematic review of existing literature related to VTE in the pediatric orthopaedic population, to estimate the overall incidence of VTE and identify risk factors associated with this condition. Methods:. A systematic review of the available literature was performed to identify articles that described VTE in pediatric orthopaedic surgery or admission. Literature queries were performed to identify articles published from 1980 to 2021 that included patients ≤21 years of age. A stepwise search strategy of 5 electronic databases yielded 1,426 articles, which were filtered by 2 reviewers to identify 30 articles for full-text review. The primary aim was to determine the rate of VTE, and the secondary aim was to identify risk factors for VTE. The pooled incidence of VTE was estimated and reported in cases per 10,000. Studies were stratified by study size, by trauma versus elective surgery, and by orthopaedic subspecialty. Results:. The 30 articles reported 3,113 VTE events in 2,467,764 pediatric patients (including those with non-orthopaedic conditions), for a pooled VTE incidence of 20 events (95% confidence interval [CI] = 10.8 to 37.2) per 10,000. Four of the studies were excluded for incomplete data or high heterogeneity. The remaining 26 studies had 850,268 orthopaedic patients with 1,108 cases of VTE, for a pooled VTE incidence of 16.6 events (95% CI = 9.1 to 30.5) per 10,000. Studies with <10,000 patients and those involving a diagnosis of trauma had the highest VTE incidence when stratification was performed. The most frequently analyzed risk factors in 15 available studies included age, sex, obesity/body mass index, type of surgery, and use of a central venous catheter. Conclusions:. This systematic review indicated that the risk of VTE associated with pediatric orthopaedic surgery or admission remains low, at <17 events per 10,000 cases. However, orthopaedic surgeons should be aware of the most common risk factors associated with pediatric orthopaedic VTE and should pay special attention to traumatic etiologies, as these yielded the highest incidence. Levels of Evidence:. Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.